Electrochemical impedance studies on pure aluminium in carbonate solution - Fernandes, J. C. S.; Ferreira, M. G. S.; Rangel, C. M. (Journal of applied electrochemistry, 1990)
The development of lightweight Al alloys with higher specific strength and stiffness and better resistance to environmental corrosion is a priority subject in advanced materials technology. Previously, work has been done on these alloys with the aim of understanding their electrochemical behaviour in different solutions. However, for comparative purposes it is necessary to conduct electrochemical experiments on pure Al. Electrochemical impedance spectroscopy has been applied successfully to various studies involving Al alloys, but in a wide number of cases the alloy was previously anodized and sealed under different experimental conditions. Correlations were found between impedance measurements and the corrosion resistance of these alloys. The the study, a.c. impedance measurements were carried out in order to characterize the electrochemical interface in a 0.01M Na sub 2 CO sub 3 solution, but without any previous modification of the Al surface. Impedance measurements account for both the formation of a film on the metallic surface and metallic dissolution. At lower potentials the film does not completely cover the surface and diffusion controlled metallic dissolution takes place at the bare metal, whereas for higher potentials, where the d.c. current is almost stable, the a.c. response reveals a dissolution process for a surface covered with a continuous film. Graphs. 16 ref.--AA